DIFFERENCE BETWEEN GROSS MOTOR SKILLS OF INFANTS RECEIVING BREASTMILK AND RECEIVING BREASTMILK-FORMULA MILK - Eduardo, Johanes F; Susan, Susan; Parengkuan, Irene L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Development is the process of changing the functional capacity of the body's organs to a state that is increasingly organized and according to their respective functions. There are gross motor skills, fine motor skills, social skills, emotional abilities, language skills, and knowledge in the development domain. Gross motor movement is the ability to change various body positions using large muscles. Gross motor development begins before a child continues the developmental stage to the next domain. One of the factors in infant development is breastfeeding. Breastfeeding can be done as a solution to prevent delays in motor development in children.Purpose: To determine the difference between the gross motor skills of infants receiving breastmilk and receiving breastmilk-formula milk in Gotong Royong Hospital.Method: This study used an observational analytic study with a research design retro cross-sectional. The sampling technique was carried out by random sampling. The data collection procedure was carried out by collecting secondary data based on medical records from the main study, "The Impact of Early Initiation of Breastfeeding on the Health Profile of Mother and Infant in Gotong Royong Hospital". In this study, using the statistical test Chi-square then data analysis was performed using software SPSS on the computer.Results: Based on the analysis test, there was no difference in gross motor development of infants aged three months who were breastfed and those who were breastfed and received formula milk with a value of p = 1,000 (p <0,05). Babies who experienced gross motor development were suspected (42%), while those who experienced normal gross motor development were (58%).Conclusion: There is no difference in gross motor development of infants aged three months receiving breastmilk and breastmilk-formula milk in Gotong Royong Hospital.